Continuous catalyst-free biodiesel synthesis from rice bran oil fatty acid distillate in a microreactor - Nattee Akkarawatkhoosith; Amaraporn Kaewchada; Attasak Jaree (Energy Reports, 2020)
This work proposed the catalyst-free biodiesel synthesis from the low-grade feedstock. Rice bran oil fatty acid distillate (RBOFAD) containing 65.5% of free fatty acids and ethanol were applied as a feedstock. The influence of operating parameters including residence time, reaction temperature, and ethanol-to-oil molar ratio on the biodiesel content (%Ester) were investigated. The experiments were carried out in a microreactor under the supercritical conditions. It was found that all parameters were important for achieving high %Ester. The optimal conditions for obtaining high biodiesel content (75%) were as follows: reaction temperature of 300~°C, ethanol-to-oil molar ratio of 5:1, and residence time of 24 min. The potential enhancement of this synthesis was studied through the addition of either iso-propanol or acetic acid which acted as a co-reactant. Unfortunately, both additives did not increase the %Ester further over the range of operating conditions studied.
Keywords: 330; Biodiesel; Additive; Microreactor; Rice bran oil fatty acid distillate; Supercritical